2008
DOI: 10.1677/joe-07-0522
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor/c-Kit signalling in normal and androgenetic alopecia hair follicles

Abstract: Androgens stimulate many hair follicles to alter hair colour and size via the hair growth cycle; in androgenetic alopecia tiny, pale hairs gradually replace large, pigmented ones. Since stem cell factor (SCF) is important in embryonic melanocyte migration and maintaining adult rodent pigmentation, we investigated SCF/c-Kit signalling in human hair follicles to determine whether this was altered in androgenetic alopecia. Quantitative immunohistochemistry detected three melanocyte-lineage markers and c-Kit in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 95 publications
(118 reference statements)
0
51
0
Order By: Relevance
“…The binding of SCF to c-kit transactivates the receptor tyrosine kinase to activate stem cells, and the SCF/c-kit signaling induces cell survival, differentiation, and proliferation; the latter is evidenced by the cell proliferation marker Ki-67 [8, 18, 30]. In the hair follicle, the cells of the keratinocytic and melanocytic lineage are responsible for hair growth and color, respectively, and express c-kit [4, 25, 26, 29], while stromal cells in the dermis produce SCF [4, 28]. Thus, it is conjectured that the SCF/c-kit signaling is involved in the pathological processes of AAR and AGA.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of SCF to c-kit transactivates the receptor tyrosine kinase to activate stem cells, and the SCF/c-kit signaling induces cell survival, differentiation, and proliferation; the latter is evidenced by the cell proliferation marker Ki-67 [8, 18, 30]. In the hair follicle, the cells of the keratinocytic and melanocytic lineage are responsible for hair growth and color, respectively, and express c-kit [4, 25, 26, 29], while stromal cells in the dermis produce SCF [4, 28]. Thus, it is conjectured that the SCF/c-kit signaling is involved in the pathological processes of AAR and AGA.…”
Section: Introductionmentioning
confidence: 99%
“…During ageing, androgens stimulate many hair follicles to alter hair colour and size via the hair growth cycle. The stem cell factor (SCF)/c-Kit signalling pathway, which is important in embryonic melanocyte migration and maintaining adult rodent pigmentation has been suggested to be involved in this process [48 ]. In addition, it has been demonstrated that androgens lead to changes in transcription of genes in the DPC, which regulate hair growth and the hair growth cycle [49,50].…”
mentioning
confidence: 99%
“…They are localized in the outer layer of the outer root sheath of the infundibulum and midfollicle and the matrix of the hair bulb. [7] Comparison of epidermal and follicular melanin units[8] reveals that there are certain important differences between both of them. The ratio between keratinocytes and melanocytes is 1:6 in hair follicle whereas it is 1:36 in epidermis.…”
Section: Discussionmentioning
confidence: 99%